The special parents for special children: A qualitative study - Ersy Azheema Huda; muzayyanah, nurul (Universitas Muhammadiyah Malang, 2023)
Parents of children with special needs (CSNs) have a unique responsibility to care for and assist in the development of their children. It often leads to psychological adjustments. This study aimed to find empirical evidence of how parents of CSNs with low education and socioeconomic status experience positive psychological adjustments to their CSN. The study used triangulation methods, including focus group discussions, in-depth interviews, and observations, involving seven parents of CSNs. Through an intentional data reduction process, three main themes emerged regarding the manifestation of psychological adjustment in parents of CSNs. These themes are (a) acceptance of the CSN's condition, (b) resilience in parenting CSNs, and (c) anxiety about the CSN's future. The study found that accompanying the growth and development of children with special needs is not an easy journey. Furthermore, parents of CSNs with low education and economic status were delayed in receiving certainty from doctors regarding their child's 'special condition.' However, the parents in this study exhibited positive psychological adaptability. They were able to develop acceptance and resilience and successfully reduce anxiety through patience and faith in Allah SWT. Keywords: children with special needs, parents, acceptance, resilience, anxiety